Factors Related to The Compliance of Medan Johor Public Health Center Hajj Pilgrimages in Returning The Health Alert Cards of 2024 Hajj Pilgrimages - Elidatati, Elidatati; Santoso, Heru; Hutajulu, Johansen; Nababan, Donal; Sembiring, Rinawati (Griya Eka Sejahtera, 2025)
Background: The Hajj pilgrimage is an obligation for Muslims, as established in Constitution Number 8 of 2019. One of the important components in the organisation of the Hajj is health, especially due to the high proportion of elderly and chronically ill congregants, who are considered a high-risk group. The Hajj Pilgrim Health Alert Card (K3JH) is issued to detect infectious diseases early after the congregation returns home. However, the rate of K3JH returns in Medan City has not yet reached the target of 90%.Methods: This study employed a cross-sectional design and was conducted at the Medan Johor Health Centre in 2024. The research sample consisted of all Hajj pilgrims registered in the work area. Data were collected through questionnaires and documents monitoring K3JH returns. The variables analysed included age, gender, education, occupation, distance to health facilities, disease status, information received, and the mechanism of K3JH return. Data analysis was performed using chi-square tests and logistic regression.Results: The majority of congregants who did not return their K3JH cards were elderly individuals with accompanying diseases. The main reasons for not returning the K3JH were forgetfulness, loss of the card, and lack of communication. Significant factors associated with K3JH return included age, education, disease status, and access to health services.Conclusion: Compliance among pilgrims in returning the K3JH is influenced by both individual and systemic factors. There is a need for targeted education, effective communication strategies, and strengthened coordination between health centres and KBIHU to increase the rate of K3JH returns. The results of this research have important implications for community health policy and the prevention of infectious diseases among Hajj pilgrims.